“Control interno en el área de inventario y su impacto en la rentabilidad del almacén de pinturas Bonilla, cantón La Maná, periodo 2020”. - Cobeña Zambrano, María Angélica (2023)
El Almacén de Pinturas Bonilla, which is a marketer of articles related to decoration and adaptation of interiors and exteriors. The inventory of this company has been an item little considered, a situation that has given rise to a series of inconveniences that have affected the profitability of the organization. The elaboration of the present investigation, has as objective to elaborate an Internal Control model in the inventory area to be able to establish its impact on the profitability of the Pinturas Bonilla Warehouse, La Maná canton, period 2020. That is why as part of the methodology used the logical historical method, the inductive, deductive and analytical method was used. Among the types of research used, applied, bibliographic, qualitative and quantitative field research was used. To diagnose the current situation in the company's inventory area, the interview technique was used, the same one that was applied to the company's Manager. In order to establish the internal control of the inventory, COSO I internal control questionnaires were applied, based on the components of Control Environment, Risk Assessment, Control Activities, Information and Communication, and Supervision. Among the results obtained, it was possible to identify that the company lacks an internal control manual in the inventory area. Among the most relevant results obtained from the application of financial indicators, it is reflected that the owners or investors of the company are currently not receiving any return on their contributed capital. The application of the COSO I questionnaire reflects that the level of confidence calculated in a consolidated manner, corresponding to all the components of the internal control questionnaire COSO I, was 73%, the same one that is located in the MODERATE range, while the level of The calculated risk was 27%, the same one that is located in the MODERATE range, in addition to evaluating the profitability of the company, the Operational Profitability indicator, the Capital or Equity Profitability indicator, and the Net Profitability indicator were applied. Finally, as proposal, an internal control model was designed for the inventory area of the company Almacén de Pinturas Bonilla. It is concluded that the company does not have formally defined internal control procedures in the inventory area. The implementation of the proposal of an internal control model for the inventory area is recommended.